Aquatic exercise and mental health: A scoping review - Morgan Jackson; Manjot Kang; James Furness; Kevin Kemp-Smith (Elsevier, 2022)
Objectives: The aims of this review were to 1) summarise the breadth and types of research regarding the impact of aquatic exercise on mental health completed to date, 2) provide a clear indication of the intervention type, volume, measurement tools used, and populations best served in relation to this activity and its effectiveness and 3) to identify domains within the literature that can be developed so recommendations can be made for future investigations. Method: A scoping review was performed under the PRISMA guidelines. A systematic search of Pubmed, SPORTDiscus, PsycInfo and Google Scholar databases was conducted. Studies observing the effect of aquatic exercises on mental health and related parameters were considered for inclusion. The data from the selected studies were then extracted and analysed methodically. Primary conditions measured: Depression, anxiety, mood, self-esteem, and psychological well-being were the primary mental states for which findings could be clearly extracted. Results: Of the 1635 articles that resulted from the search, 23 articles met all inclusion criteria. Of these, 12 were randomised controlled trials. Cumulatively, the findings of this review trend towards aquatic exercise being effective in generating positive changes in mental health. Conclusion: Aquatic exercise, specifically winter swimming, leisure swimming, competitive swimming and aquatic aerobics, can be a promising conservative therapy for mental health management. However, it is recommended that further research be conducted to solidify these findings and establish the long-term effects of this intervention on mental health.